Implementation of egg incubator control system at La Tansa Firdaus Farm Purwakarta - Zakaria, Diky; Abdullah, Ade Gafar; Fauzi, Ahmad; Suranegara, Galura Muhammad; Haryanto, Excel Thrive Valerian; Ramadhan, Muhammad Raihan; Ferdinand, Edgard Altamerano; Nugraha, Rifki Destrizal (Jurnal Abmas, 2026)
Chicken farming is a promising business opportunity, as most Indonesians enjoy chicken meat and eggs. This community service program aims to improve the hatching success rate of free-range chicken eggs at La Tansa Firdaus Farm through the implementation of an Internet of Things (IoT)-based Egg Incubator Control System. Partners previously used conventional incubation methods with incandescent lamps, yielding a success rate of only 70-75%. The program was implemented using a Participatory Action Research (PAR) approach through several stages, including problem identification, system design, material development, training, implementation, and monitoring and evaluation. Three modified incubators with automatic temperature control systems and a web-based monitoring dashboard were donated to partners and implemented. In addition to technical training on incubator use, digital marketing training was also provided to improve the competitiveness of livestock products. Evaluation results showed that partners gained increased technical capacity, understood how to operate and maintain the system, and expressed the hope that this technology could increase the hatching success rate to 80-85%. Partners also demonstrated a commitment to implementing and developing the technology sustainably. This program proves that simple IoT-based technological innovations can have a real impact on increasing the productivity of smallholder livestock farming.
Keywords: community empowerment; egg incubator control system; hatching system; Internet of Things